The Influence of Medialization to Legal Discourse Concerning Context, Media and Social Power - Annikki Koskensalo (David Publishing Company, 2026)
Medialization has become like digitalization, rationalization, dynamization, globalization, pluralization, hybridization, and differentialization and is one of the buzzwords of modern Western industrialized societies, which are all together essentially responsible for structural change in communication. Medialization means the adaption of producers to media logics, media formats, and media routines & workflows. There are consequently and logically influences because of the dynamic process of medialization to legal discourse and genres, law, media, and social power. It has to be discussed if the logics, data formats, and routines & workflows of new media and information and communication technologies (ICTs) like social media are creating also a new generation of genres and novel form of legal discourses. Also, if social media will replace or complete old classic media (law of Riepl), the question of the relevance of law concerning new & social media has to be answered in close future. Lastly, if to the fore of social power, these new novel resources are actually framing for problem-based inquiries in law. There are big chances but also serious risks in cyberworld, their realities, and dangers. There actually exists an urgent call of action to theory building, development of methodologies, and empirical research.